The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.ultras.2021.106372
|View full text |Cite
|
Sign up to set email alerts
|

Supervised learning strategy for classification and regression tasks applied to aeronautical structural health monitoring problems

Abstract: This paper presents the use of a kernel-based machine learning strategy targeting classification and regression tasks in view of automatic flaw(s) detection, localization and characterization. The studied use-case is a structural health monitoring configuration with an array of piezoelectric sensors integrated on aluminum panels affected by flaws of various positions and dimensions. The measured guided wave signals are post processed with a guided wave imaging algorithm in order to obtain an image representing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Several ML methods have been developed in the last few years to solve various SHM and damage detection problems, especially by using neural networks (NN) [ 1 , 2 , 3 , 4 , 5 ]. Even though ML methods are already well established in vibration-based SHM [ 6 ], their use in guided wave-based SHM is currently rising [ 7 , 8 , 9 ]. For instance, Roy et al [ 7 ] described an unsupervised learning approach for structural damage identification under varying temperatures based on an NN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several ML methods have been developed in the last few years to solve various SHM and damage detection problems, especially by using neural networks (NN) [ 1 , 2 , 3 , 4 , 5 ]. Even though ML methods are already well established in vibration-based SHM [ 6 ], their use in guided wave-based SHM is currently rising [ 7 , 8 , 9 ]. For instance, Roy et al [ 7 ] described an unsupervised learning approach for structural damage identification under varying temperatures based on an NN.…”
Section: Introductionmentioning
confidence: 99%
“…Their methodology is validated with measurements from coupon samples in a uniaxial testing machine. More recently, Miorelli et al [ 8 ] demonstrated that support vector machines (SVM) trained on numerical data can be used to solve the inverse problem for damage detection and sizing from experimental guided wave (GW) images. They used a circular array of transducers on an isotropic metal plate with through-holes of different sizes modelled at different locations.…”
Section: Introductionmentioning
confidence: 99%
“…A broader and more comprehensive discussion can be found in [97,98], which are two fundamental texts for all people working on SHM. Moreover, supervised learning strategy for classification and regression tasks applied to aeronautical SHM problems was discussed in detail by Miorelli et al [99].…”
Section: Structural Health Monitoringmentioning
confidence: 99%
“…-Decision tree (DT): DT is a supervised learning method. DT constructs the learning model using a set of IF-THEN rules obtained from the training set to predict the output class [88,89]. The hierarchical tree is created based on features in the dataset.…”
mentioning
confidence: 99%
“…-K-nearest neighbor (KNN): It is the simplest supervised learning method. It is known as a lazy learning scheme [87,88]. In this method, we determine the class of the new sample as follows: first, we compare this sample with the training dataset to determine the k closest samples in the training set.…”
mentioning
confidence: 99%